Congestive Heart Failure dan Atrial Fibrilasi - Mirza Hidayatsyah; Emelda Emelda (Jurnal Ventilator, 2024)
Congestive heart failure is a pathophysiological condition in which the heart as a pump is unable to meet the need for blood for tissue metabolism. It has been reported that a 56-year-old patient with complaints of shortness of breath is felt to be worse when sleeping in a supine position and improves when sitting in a sitting position. The complaint was accompanied by chest pain that radiated to the back and left arm and palpitations. Patients also complain of getting tired easily when doing activities even to walk to the bathroom. On physical examination, it was found that irregular S1-S2 was accompanied by a murmur. On the examination of ECG and Echocardiograph, it was found that the picture of AF and EF was 41%. In the thorax photo examination, cardiomegaly. The management of this patient is the administration of drugs that reduce shortness of breath and chest pain in patients.